Exploring Fantasy Theme Analysis: Unravelling Fandom Dynamics in BTS ARMY - Arny Aurora, Raden; Puspita, Virienia; Maharani, Anissa; Wiranito, Nico (Action Research Literate, 2024)
In the digital era, fan communities have evolved into sanctuaries of liberation and empowerment, providing enthusiasts with spaces for uninhibited self-expression, diverse perspective exchanges, and identity exploration. Using a qualitative phenomenological approach, the research examines the construction of collective identity and meaning-making among BTS fans.The analysis reveals that the BTS ARMY Indonesia community adopts fantasy themes such as "APOBANGPO" (ARMY Forever, Bangtan Forever), "Yoongi Marry Me," and "Racist Billboard." The shared adoption of these themes fosters a sense of unity, emotional connection, and collective identity among fans.Through detailed examination, this study demonstrates the effectiveness of FTA in understanding fan community dynamics. It highlights how BTS fans in Indonesia construct and negotiate their identities through shared fantasies, contributing to a supportive and interconnected global fandom. The findings underscore the importance of participatory culture in providing safe spaces for fans to experiment with new passions and activities, ultimately fostering personal growth and community cohesion.